Ação docente, formação em serviço e metodologias ativas com o uso das TDIC em tempos de pandemia - Gengo, Priscila Lopes Garcia de Oliveira (2023)
This research work was developed along the master studies in the Graduate Program in Education: Curriculum, research of New Technologies in Education, by the Pontifical Catholic University of São Paulo, investigating the methodological practices used by teachers at a private school in the city of São Paulo/SP and the in-service training offered to them. This study shows a qualitative and collaborative approach carried out with three 6th grade teachers, middle school, initially in the context of remote teaching and later in the context of mixed classes (part of the students at home and part of the students at school), due to the pandemic caused by the Covid-19 virus. To collect data, recordings of three classes and recordings of three recall stimulation interviews (PACHECO, 1995) of each teacher were used. This consisted of interviewing the teachers while they individually attended their classes with the researcher who questioned them about the images, trying to make them remember the strategies used at the moment, provoking a reflection about their practices and the conception of the subjects. Recordings were also collected in the researcher's diary and the interventions carried out during the observation of each of the classes and, finally, the background of the teachers’ training courses carried out throughout the research, with the objective of understanding whether the methodologies used by the teachers showed evidence of active methodologies with the use of DICTs and if the in-service training developed by the school provided a reflexive action and/or a change of conceptions. Data analysis was carried out through a proposal called prose analysis (ANDRÉ, 1983). The research revealed that the teacher training offered by the school contributed significantly to the learning of new technologies and their use, as well as to a change in practices and conceptions about the methodologies that allow students leadership in the search for knowledge. The study also showed that the situations of sharing knowledge and experiences among peers (teachers) as well as collaboration were very effective, being strong aspects to be considered. Finally, it is highlighted that the research involved concepts such as homology of processes, ubiquitous learning and pedagogical isomorphism as possibilities for training strategies